Framework for ERP implementation in the context of Moroccan SMEs - Zouhair, Yassine; ELMRINI, Younous; BELAISSAOUI, Mustapha (Data and Metadata, 2025)
The current and future challenges and the rapid evolution of markets in a context of globalization require companies to acquire the technological tools to manage information flows in order to remain up-to-date and competitive. To do so, it is ready to deploy important means to guarantee its competitiveness and its scalability. This is done mainly through the implementation of software technologies, the most popular of which are known as Enterprise Resource Planning (ERP). ERP is a popular option for small and medium-sized enterprises (SMEs) today that are looking to optimize and integrate their information systems. However, the implementation of ERP is a complex process and remains a challenge for many SMEs, even more so than for large companies, where ERP integration failures have caused some to go bankrupt. In addition, SMEs differ in a number of characteristics that can affect the implementation of ERP, so it is not wise to use the frameworks developed for the large enterprises to implement Enterprise Resource Planning Systems (ERPS) in SMEs. The objective of this research is to develop a framework for implementing an ERP in the context of Moroccan SMEs. The developed framework was used for implementing an ERPS in two Moroccan SMEs, it includes 5 phases, for each one, the objectives, critical success factors, inputs, processes, outputs and risks to be considered. This research study contributed to both practice and research, and the results could help practitioners and Moroccan SMEs when implementing an ERP and to suggest directions for future research.